Forgotten alliances: Japan’s role in World War I and its enduring impact on Southeast Asian geopolitics - Habib Badawi (Southeast Asia)
Purpose – This paper investigates Japan’s significant role as an Allied power during World War I, exploring its motivations, military contributions and postwar geopolitical ambitions. Design/methodology/approach – Employing a meticulous analysis of primary sources such as historical documents and personal accounts, alongside secondary sources including scholarly articles and books, this study aims to provide a comprehensive understanding of Japan’s decision-making processes during the war. A comparative examination of Japan’s military contributions to the Allied Powers, particularly in securing sea lanes across the West Pacific and Indian Oceans, is conducted to assess their impact on the overall war outcome. Additionally, diplomatic records and negotiations are scrutinized to unravel Japan’s postwar geopolitical objectives, with a focus on its efforts to expand its influence in China. Findings – The research reveals the multifaceted engagement of Japan in World War I, highlighting its motivations, military actions and postwar ambitions. Japan’s contributions to securing sea lanes and its postwar endeavors to enhance influence in China emerge as significant findings. Research limitations/implications – The study’s reliance on historical documents and secondary sources may entail limitations in accessing comprehensive data, potentially impacting the depth of analysis. Furthermore, interpretations of events and motivations may vary based on different scholarly perspectives. Practical implications – This study has practical implications for understanding the political and geopolitical context of Japan’s involvement in World War I and its aftermath. By recognizing Japan’s motivations and actions during this period, policymakers and international relations scholars can gain insights into the complexities of imperial ambitions, nationalism and power dynamics in global politics. Understanding these historical implications can inform contemporary discussions about regional stability, alliances and nationalism’s impact on international relations. Furthermore, this research encourages critical analysis of historical narratives and promotes a nuanced understanding of the consequences of imperialistic pursuits in shaping present-day dynamics. Social implications – This study fosters a deeper understanding of the historical context and the impact of imperialism on society. By examining Japan's involvement in World War I and its subsequent imperialistic ambitions, the study sheds light on the complexities of nationalism, racial superiority and ideological justifications for expansion. This understanding can help societies reflect on the dangers of chauvinistic nationalism and its potential consequences. By critically analyzing historical events, societies can develop a more inclusive and empathetic perspective. This will promote dialogue, tolerance and the appreciation of diverse cultures in the pursuit of a more harmonious and equitable world. Originality/value – By combining a thorough examination of primary materials with a comprehensive review of scholarly discourse, this paper offers a nuanced and well-rounded perspective on Japan’s involvement in World War I and its enduring geopolitical consequences. It contributes to the understanding of Japan’s role as an Allied power and its postwar ambitions.